Pengaruh Gaya Belajar Terhadap Pembelajaran Orang Dewasa Berbasis LMS [The Influence of Learning Styles on LMS-Based Adult Learning] - Retnani, Mega Astuti Dwi; Afrista, Esgi; Elsaday, Rut Sulistiowati (Jurnal Teropong Pendidikan, 2024)
Utilization of LMS as a learning platform can now be utilized by various groups, including the Master of Educational Technology program at Pelita Harapan University. The use of this LMS is, of course, related to the student's learning style. The use of VARK is used to determine student learning styles and then connect it to their learning experiences using the LMS. This research was conducted by conducting interviews with 30 Master of Educational Technology students at Pelita Harapan University, batch 49 and 50. The research method used in this research was using a quantitative approach with an instrument in the form of a questionnaire. The analysis technique in this research is to present facts in the form of numbers by providing an explanation of quantitative data. The results of the analysis with Pearson Product-moment obtained an RXY value of 0.254 for Visual, 0.420 for Aural, 0.325 for Read, 0.409 for Kinesthetic with a value of 0.05 and a Df of 28. The correlation coefficient shows a value of 0.361, which means that the use of LMS with Visual and Read learning styles has an unrelated relationship. Meanwhile, Aural and Kinesthetic learning styles have a significant correlation.